KENAKALAN ANAK (JUVENILE DELIQUENCY) DAN UPAYA PENANGGULANGANNYA - Raihana SH.,MA (UIR PRESS, 2016)
Children is nation future asset and router generation dream of nation, so children is entitled to the continuity of life, growth and develop, participating and entitled of protection from discrimination and also have civil rights and freedom. Currently juvenile deliquency has leaded into criminal behaviour as the result the case of children in conflict with the law arises. The efforts to overcome the matters of juvenile delinquency is continuously performed. However, such approaches to prevent and to overcome juvenile deliquency that exist today, Some approaches to prevent and address the child's misbehavior is happening this moment appropriate more done through repressive approach. Moreover, imprisonment to children in conflict with the law is still a very prominent way. The appropriate methode and approach to overcome the matters of juvenile delinquency should be performed and based on deep understanding on the causes of juvenile deliquency. There are Penal and Non Penal facility that should be equally in understand and this article aims to discuss the causes of child delinquency is good from the perspective of the theory as well as the concept and also the scope of the law and the method to resolve the delinquency of children in Indonesia. Keywords: juvenile deliquency, effort to overcome it.